The Effect of Cooperative Learning Model Make a Match Type on Mathematical Problem Solving Ability in Equation of Absolute Value - Ismi Widyaningrum; Tati Ariyah; Linda Linda; Ira Asyura (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2022)
The purpose of this study was to find out how the effect of cooperative learning model Make A Match type on students of class X in Madrasah Aliyah MALNU Menes Center to solve mathematical problem in equation of absolute value. In this study, the author used a quasi-experimental type of quantitative research method. This study involved two classes, namely the control class and the experimental class. The results of this study indicated that there were difference in the students’ final ability of mathematical problem solving between the experimental class and control class. This could be seen from the active learning, student curiosity was very high in the experimental class than in the control class. In conclusion, the Make A Match learning model has an effect on students’ ability to solve mathematical problem.